Eating, Drinking, Smoking, and Testing the Lifecycle Hypothesis - Browning, Martin (Quarterly Journal of Economics, 1987)
This paper presents some evidence on expenditure patterns over the lifecycle that has a direct bearing on the question of whether households are significantly credit constrained. Our particular test looks at the consumption of food, alcoholic beverages, and tobacco to see whether the consumption of the latter two “goods” falls as couples have children. The latter usually involves a decrease in household current income and an increase in needs. If households are not credit constrained, they should maintain their consumption of alcoholic beverages and tobacco. We find no significant decrease in the consumption of these goods.